Review of 130 years of research on cyanobacteria in aquatic ecosystems in Serbia presented in a Serbian Cyanobacterial Database (Advances in Oceanography and Limnology, 2017)
The presence of toxic cyanobacteria in aquatic ecosystems in the territory of the Republic of Serbia was surveyed over a period of several decades. Increasing attention is being paid to some negative consequences that may be caused by these microorganisms. Information from available literary sources regarding the distribution and frequency of cyanobacteria and their toxins over a period of 130 years, together with the effects on humans and wildlife in aquatic ecosystems, were gathered and incorporated into a Serbian Cyanobacterial Database created for the CYANOCOST Action. This database encompasses information on 65 aquatic ecosystems, including rivers, lakes, ponds, canals, irrigation reservoirs, reservoirs used for drinking water supply and reservoirs used for other purposes. Cyanobacterial blooms were found in almost 80% of the investigated aquatic ecosystems. The analysis of the research showed the presence of more than 70 species, including blooms of 24 species from 13 genera. Five species of cyanobacteria: Microcystis aeruginosa, Aphanizomenon flos-aquae, Planktothrix agardhii, Microcystis flos-aquae and Planktothrix rubescens frequently formed blooms in the investigated waterbodies and cyanotoxins were also detected in some of them, which had certain negative effects. Here, we present an overview of data contained in the Serbian Cyanobacterial Database, concerning cyanobacterial distribution, cyanotoxin production and associated biological effects in different types of water bodies from the Republic of Serbia. Also, recent important and major cases of cyanobacterial blooming in reservoirs used for drinking water supply: at Vrutci and Ćelije, the Aleksandrovac irrigation reservoir, the Ponjavica River and Lake Palić, including systematic research on the Lake Ludoš and few fishponds are further described. It can be concluded that cyanobacteria and cyanotoxins are omnipresent in different water bodies throughout the Republic of Serbia. For these reasons it is imperative to continue with the monitoring of cyanobacteria and cyanotoxins, as well as to continuously supplement the established database with new information. The Serbian Cyanobacterial Database represents a treasury of information on cyanobacteria and their toxins, and as a model for other countries in the region and beyond.
Keywords: Cyanobacterial blooms; cyanotoxins; database; historical overview.